Protector control: extension to a class of nonlinear distributed systems - Qaraai, Youssef; Bernoussi, Abdes Samed (Zielona Góra: Uniwersytet Zielonogórski)
We present an extension of the protector control scheme introduced for the linear case in a previous work to a class of nonlinear systems. The systems considered are assumed to have a finite propagation velocity while the initial state is subject to a spreading disturbance. We characterize such a control first by using the remediability approach to the resulting nonlinear delay system, and then by coupling families of transformations and the delay approach. To illustrate this work, we provide a simulation example.
Keywords: nonlinear distributed systems; disturbance; spreadability; vulnerability; remediability; protector control